ESTETIKA SASTRA POPULER DALAM NOVEL MENCARI SARANG ANGIN KARYA SUPARTO BRATA - Dheny Jatmiko (Universitas Airlangga, 2015)
This research’s title is Estetika Sastra Populer d Novel Mencari Sarang Angin Karya Suparto Brata. This research is aiming to elaborate the story of Mencari Sarang Angin by Suparto Brata. This research is done because Suparto Brata and his novels are containing historical story but, different with the other historical novels, appreciation and legitimation that received by Suparto Brata is not relatively significant.Mencari Sarang Angin is one of Suparto Brata’s popular work, that is the reason why this work becomes the object study. There are some theories that is used, they are cultural production by Bourdieu and detective formula theory. According to this research, there are two findings, they are dominant love story as the main story, also utilization of detective story formula as the structure of story telling.